Manajemen Mutu Pembelajaran Di SMAN 1 Bintang Bayu Serdang Bedagai Sumatera Utara - Sugianto Sugianto; Siti Patimah; A.Latief Arung Arafah; Andi Warisno (Departement of Mathematics Education, 2024)
This examination means to portray the administration of Learning Quality at SMAN 1 Bintang Bayu Serdang Bedagai, North Sumatra. This sort of exploration is subjective. The methods utilized as information assortment apparatuses in this examination are interview, perception and documentation strategies. The consequences of the exploration show that the Quality Administration of Getting the hang of Arranging at SMAN 1 Bintang Bayu Serdang Bedagai Sumatera Utarahas worked out in a good way, to be specific completing preparation, coordinating, handling time, choosing media and strategies as illustrated in the RPP and Schedule. Then, at that point, the Quality Administration of Learning Execution at SMAN 1 Bintang Bayu Serdang Bedagai, North Sumatra has additionally been carried out well, where educators complete opening exercises, center exercises and shutting exercises. Moreover, Quality Administration of Learning Assessment at SMAN 1 Bintang Bayu Serdang Bedagai, North Sumatra has been executed actually, in particular educators do assessment arranging in view of Skill Principles and Fundamental Abilities, evaluations are completed in a coordinated way and in light of appraisal pointers. furthermore, there is follow-up as therapeutic and advancement for understudies. Aside from Quality Administration, Learning Management has additionally been executed well at SMAN 1 Bintang Bayu Serdang Bedagai, North Sumatra, to be specific the oversight of learning execution is completed straight by the school head.